The effect of rescuers' body mass index on chest compression performance during simulation training in Hong Kong - Annemarie Hor Wan Cheung; Vico Chung Lim Chiang; Esther Suk Bing Mok (Halla Newcastle Education and Research Center, 2016)
Background: High quality cardiopulmonary resuscitation (CPR) is crucial in out-of-hospital or in-hospital cardiac arrests, but the quality of chest compressions varies in different rescuers. Body mass index (BMI) had an effect on chest compression performance, especially the compression depth. Objectives: To evaluate the effect of BMI on chest compression performance through simulation training among student nurses in Hong Kong. Methods: A longitudinal observational study with repeated measures of an equivalent group of 99 student nurses was performed, with the pre-test performed immediately before the adult basic life support provider course, followed by an immediate post-test, and a retention-test four weeks later. Chest compression performance was assessed and evaluated between the three consecutive simulated skills tests. Results: Body mass index was found to have significant effects on the overall mean chest compression depth that the overweight participants compressed better than other BMI groups for the three time points of evaluation. However, being overweight did not warrant sufficient chest compression depth, nor complete chest recoil. Conclusions: The higher the BMI was, the deeper the chest compressions were. However, with the higher the BMI, higher incidence of incomplete chest recoil was noted. Despite the above, BMI had no clear effect on other CPR quality. Most participants had difficulty in achieving the recommended compression depth even after training. Simulation training of CPR for high quality chest compression should continue to focus on the practice of chest compression depth and complete chest recoil.